2017
DOI: 10.21873/anticanres.11767
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Combination Therapy with MET and VEGF Inhibitors for MET-overexpressing Glioblastoma

Abstract: The current data indicate that the inhibition of both MET and VEGF exhibits efficient therapeutic effects of GBM-bearing hosts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Studies have demonstrated that VEGF is overexpressed in gastric, lung, colorectal, breast, prostate, liver cancer and other solid tumors (27,28). Recent studies have reported that the expression of VEGF in esophageal cancer is associated with lymph node metastasis, distant metastasis and clinical stage (P<0.05), but there is no significant correlation with pathological grading and depth of invasion (29,30). Additionally, overexpression of VEGF suggested poor prognosis of esophageal cancer, a meta-analysis reported that the risk of late stage (III and IV) increased in esophageal cancer patients with VEGF overexpression (HR=1.55), and the odds ratio (OR) was 2.14 (31).…”
Section: Discussionmentioning
confidence: 95%
“…Studies have demonstrated that VEGF is overexpressed in gastric, lung, colorectal, breast, prostate, liver cancer and other solid tumors (27,28). Recent studies have reported that the expression of VEGF in esophageal cancer is associated with lymph node metastasis, distant metastasis and clinical stage (P<0.05), but there is no significant correlation with pathological grading and depth of invasion (29,30). Additionally, overexpression of VEGF suggested poor prognosis of esophageal cancer, a meta-analysis reported that the risk of late stage (III and IV) increased in esophageal cancer patients with VEGF overexpression (HR=1.55), and the odds ratio (OR) was 2.14 (31).…”
Section: Discussionmentioning
confidence: 95%
“…Bevacizumab is a humanized anti-VEGF monoclonal antibody that was approved by the FDA in 2009 for the treatment of recurrent glioblastoma. By targeting the VEGF pathway, it does not only inhibit angiogenesis but also alleviates BBB permeability and peritumoral edema (4,7,8).…”
Section: Results: Nivolumab a Human Anti-pd-1 Effectively Inhibited T...mentioning
confidence: 99%
“…Bevacizumab is a humanized anti-VEGF monoclonal antibody that was approved by the FDA in 2009 for the treatment of recurrent glioblastoma. By targeting the VEGF pathway, it does not only inhibit angiogenesis but also alleviates BBB permeability and peritumoral edema (4,7,8).The synergy between the innate and adaptive immune systems is crucial for achieving antitumor immunity, which involves the combined action of both immune responses to effectively suppress tumors (9). CD8 + T cells, also known as cytotoxic T lymphocytes (CTLs), play a vital role in the immune response against tumors by eliminating tumor cells 1991…”
mentioning
confidence: 99%
“…Though anti-VEGF therapy has been widely used and has shown benefits in the reduction of vasogenic edema associated with this disease, the overall survival benefit and resistance to therapy are yet to be improved. However, several approaches using combination therapy with radiotherapy, immunotherapy, cytotoxic drugs etc., in addition to anti-VEGF therapy showed improved results [45,46]. A recent study on combination therapy with platelet-derived growth factor (PDGF) inhibitors showed more promising results when combined with anti-VEGF therapy in terms of survival benefit and sensitization to therapy [47].…”
Section: Ceramide Signalingmentioning
confidence: 99%